Gender and age-related features in office and home blood pressure control in patients with uncomplicated hypertension in real clinical practice - Amosova K.M.; Rudenko Iu.V. (Medičnì Perspektivi)
The aim of our work was the assessment of effectiveness of standardized algorithmic treatment based on fixed-dose combination of perindopril/amlodipine and gender and age-related differences for office and home blood pressure control in real clinical practice. Our study included 421 patients with uncomplicated arterial hypertension 204 (48.5%) patients aged 60 years and older, 78 (18.5%) men (group 1), 126 (29,9%) women (group 2) and 217 (51,5%) patients younger than 60 years, 115 (27,3%) men (group 3) and 102 (24,2%) women (group 4). Home and office blood pressure measurements were performed with the standardized oscillometric automatic device with individually selected cuff. At visit 1, patients were given training and written instructions for home blood pressure measuring and recording (twice per day for 7 consecutive days before each of 5 next visit) and were prescribed a fixed-dose combination of perindopril/amlodipine, which, if needed, was followed by consecutive addition of indapamide SR, spironolactone, and moxonidine or doxazosin for target office blood pressure achievement (<140/90 mm Hg). We have identified gender and age-related differences in home blood pressure control, including lower incidence of achievement of recommended level (<135/85 mm Hg) in men younger of 60 years compared to women of the same age and persons over 60 years of both genders, which resulted in a greater incidence of masked uncontrolled hypertension in this group of patients at comparable level of adherence to treatment.